Theology and Religious Pluralism The Challenge of Other Religions - D'Costa, Gavin (New York Basil Blackwell, 1986)
Examines an increasingly important question facing theologians today, that of the relationship between Christianity and the other major religions of the world. How should the Churches respond, and how does pluralism affect Christianity's claim to absolute
Keywords: Christianity and other religions. Plurale samenleving. Theologie van de godsdiensten. Christentum Nichtchristliche Religion Weltreligion Non-Christian religions -- Attitudes of Christianity